2004
DOI: 10.1002/ajhb.20023
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral variation in limb articular surface dimensions

Abstract: Joint form is frequently used to interpret locomotor and manipulative adaptations and infer physical behavioral patterns in past humans, yet the precise genetic and environmental determinants of joint size are incompletely understood. The aim of this research is to assess the plasticity of limb articular dimension through the use of directional asymmetry as an indicator of mechanical stress during skeletal development. Directional asymmetry is largely attributable to differential mechanical loading during bone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
2
6

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(72 citation statements)
references
References 35 publications
4
55
2
6
Order By: Relevance
“…Although FEB has a median of zero, the Wilcoxon signed-ranks test reveals that a significantly higher number of individuals have right-biased %DAs (352 rightbiased versus 239 left-biased). Also, in contrast to the results of a previous study (Plochocki, 2004), femoral head diameters are significantly right biased in %DA, although the average asymmetry is quite small (0.1%). Table 4 shows the percentage of the sample (overall, male, and female) with greater than AE0.5%DA, with results that are consistent with all of these observations.…”
Section: Asymmetry In the Total Pooled Samplecontrasting
confidence: 56%
See 1 more Smart Citation
“…Although FEB has a median of zero, the Wilcoxon signed-ranks test reveals that a significantly higher number of individuals have right-biased %DAs (352 rightbiased versus 239 left-biased). Also, in contrast to the results of a previous study (Plochocki, 2004), femoral head diameters are significantly right biased in %DA, although the average asymmetry is quite small (0.1%). Table 4 shows the percentage of the sample (overall, male, and female) with greater than AE0.5%DA, with results that are consistent with all of these observations.…”
Section: Asymmetry In the Total Pooled Samplecontrasting
confidence: 56%
“…Some evidence for much smaller but systematic directional asymmetry favoring the left side has been reported in the human lower limb, especially in the femur (Schultz, 1937;Latimer and Lowrance, 1965;Ruff and Jones, 1981;Plochocki, 2004;see below). This trend has been termed a ''crossed symmetry'' pattern between contralateral limbs (Schaeffer, 1928;Plochocki, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Plochocki et al [2006] reported the surface size of the femoral head to be significantly larger in growing mice with voluntary access to physical activity than in controls without such access. Plochocki [2004] also found the subchondral bone surface areas of the right upper limb to be significantly larger than those of the left upper limb in human skeletons from subjects who were supposedly right-handed. In the human second metacarpal, Lazenby et al [2008] recently also observed the mediolateral (but not the dorsopalmar) dimensions of the subchondral bone surfaces to be significantly larger on the right-hand side, but pointed out that the side differences in subarticular bone microarchitecture and diaphyseal bone geometry were quantitatively far more important than those of subchondral bone size.…”
Section: Discussionmentioning
confidence: 84%
“…Mechanical stimulation has been shown to enhance the biosynthetic activity of the chondrocytes [Sah et al, 1989;Kim et al, 1995;Buschmann et al, 1999;Jin et al, 2001;Waldman et al, 2003], and animal models have suggested that cartilage thickness may adapt to the mechanical loading conditions in healthy joints [Jurvelin et al, 1990;Oettmeier et al, 1992]. To date, however, it is unclear whether adult articular cartilage and joint morphology display phenotypic plasticity and adapt to individual loading histories [Lieberman et al, 2001;Plochocki, 2004;Plochocki et al, 2006;Lazenby et al, 2008].…”
Section: Introductionmentioning
confidence: 99%
“…Even small mechanical stresses caused by handedness may lead to deviation from symmetry in the joint surface. In a study of 80 skeletons from archaeological excavations in Missouri, Plochocki [243] studied joint spaces of the humerus, radius, femur, and tibia. In that study, measures of the joint surfaces in the upper extremities showed higher values on the right side.…”
Section: Prehistoric and Historic Skeletal Samplesmentioning
confidence: 99%